The effect of problem based learning model in writing explanation text - Suhud Aryana Suhud (Journal of diversity in learning (JDIL), 2022)
This research aims to improve the knowledge, skills and learning independence of senior high school students in writing explanatory texts based on problem-based learning models. The instrument used for knowledge test and practice test for skills. Experimental calculation instruments and data processed used Microsoft Excel 2016 and SPSS V.24. Briefly, the results of the research show 1) The ability to write explanatory texts for senior high school students whose learn used the PBL learning model is better than those used conventional learning with an average of 19.50 or 52.7% of the experimental class and 15.57 or 4.57% of the experimental class. control 2) The ability to write explanatory texts for senior high school students whose learned used problem based learning model is better than those used conventional learned with an average of 18.57 or 42.61% of the experimental class and 14.81 or 33.66% of the control class. 3) there is an association between knowledge and skills with a value of Q = 0.79. Association of knowledge with independent learning with a value of Q = 78 and the association of skills with learned independence with a value of Q = 79. 4). There are still difficulties experienced by students in solving questions and general tasks on indicators of improving the time sequence of occurrence of a sentence and the structure of the language used.